If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1y + 8x + 5y = 0 Reorder the terms: 7x + 8x + -1y + 5y = 0 Combine like terms: 7x + 8x = 15x 15x + -1y + 5y = 0 Combine like terms: -1y + 5y = 4y 15x + 4y = 0 Solving 15x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 15x + 4y + -4y = 0 + -4y Combine like terms: 4y + -4y = 0 15x + 0 = 0 + -4y 15x = 0 + -4y Remove the zero: 15x = -4y Divide each side by '15'. x = -0.2666666667y Simplifying x = -0.2666666667y
| 480ms= | | 6x+10=5x+16 | | 62=92-s | | 9+24=-4 | | 26=u-17 | | 45-3x=9-9x | | 46-j=31 | | 4x^2-20x+26=1 | | 84=x+0.2x | | 60=69-f | | 18x+14x-27y= | | 3=89-g | | 52-q=32 | | 10+12x=-56+x | | n-57=19 | | h-49=0 | | 4+3n=5(2-2n) | | 16=s-50 | | 29=q-51 | | 3a+5b=15 | | 8k+5k-10k= | | 56-d=27 | | 2+2u+7=42 | | w-10=58 | | 6=k-15 | | 4=m-63 | | 7x-3=x+7 | | 12-(3x-6)-5(7-x)= | | 39-w=2 | | y-65=9 | | (4t+9)-(-2+7)=0 | | A=p+pnr |